2017
DOI: 10.1097/igc.0000000000000870
|View full text |Cite
|
Sign up to set email alerts
|

Second Opinion Expert Pathology in Endometrial Cancer: Potential Clinical Implications

Abstract: A retrospective gynecopathological case review was shown to reveal limited but significant discrepancies in histological diagnoses as well as typing and grading of endometrial carcinomas, some directly impacting clinical management. Second opinion pathology therefore not only helps to improve the quality of translational research study cohorts but might also help to optimize patient care in difficult cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…It was shown that using a World Health Organization (WHO) two-tier classification with two diagnostic categories, hyperplasia without atypia and endometrial hyperplasia/endometrioid intra-epithelial neoplasia, improved reproducibility ( Kendall et al , 1998 ; Bergeron et al , 1999 ; Trimble et al , 2006 ; Ordi et al , 2014 ). The distinction between atypical endometrial hyperplasia and well-differentiated endometrial carcinoma showed poor intra-observer and inter-observer agreement ( Grevenkamp et al , 2017 ). Moreover, poor inter-observer agreement exists when evaluating the grade of endometrial carcinomas specifically in curettage material ( Lax et al , 2000 ; Scholten et al , 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that using a World Health Organization (WHO) two-tier classification with two diagnostic categories, hyperplasia without atypia and endometrial hyperplasia/endometrioid intra-epithelial neoplasia, improved reproducibility ( Kendall et al , 1998 ; Bergeron et al , 1999 ; Trimble et al , 2006 ; Ordi et al , 2014 ). The distinction between atypical endometrial hyperplasia and well-differentiated endometrial carcinoma showed poor intra-observer and inter-observer agreement ( Grevenkamp et al , 2017 ). Moreover, poor inter-observer agreement exists when evaluating the grade of endometrial carcinomas specifically in curettage material ( Lax et al , 2000 ; Scholten et al , 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the core strength of this study was its comprehensive analysis of DFF40 and DFF45 expression and BCL2 expression in ECs. As previous studies have reported discrepancies regarding the pathological classifications of different types of ECs, all the specimens included herein were independently re-evaluated by two experienced pathologists to confirm their diagnoses and classifications [ 48 ]. Additionally, the relatively large size of the cohort, as well as the well-defined clinical characteristics of the specimens included herein, allowed us to analyze the relationships between DFF40, DFF45, and BCL2 expression and the clinical characteristics, including OS and DFS.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of histological revision in expert centers has been seen in many neoplasms, with an impact on clinical decisions ranging between 7.5 and 23.3% [18][19][20][21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In detail, a surgical/ endoscopic resection was proposed in 4.6% of the revised cases and a change in medical treatment in 21.7%. In an additional 21.1% of patients, the histopathological reassessment led to the need for further diagnostic tests, such as an additional 18 FDG-PET/CT for complete staging of patients with G3 NEN. According to the literature for other neoplasms, the original histological report is changed by a second evaluation in expert centers in 18.0-33.3% of cases, and in our study a similar rate of significant discordance was observed (36.0%).…”
Section: Discussionmentioning
confidence: 99%